St. Thomas Christians of India: A Period of Struggle for Unity and Self-Rule (1775-87) - Anchukandathil, Thomas (Journal of Dharma, 1999)
Francis Thonippara, CMI, St. Thomas Christians of India: A Period of Struggle for Unity and Self-Rule (1775-87), Bangalore: Centre for Eastern and Indian Christian Studies (Dharmararn Vidya Kshetram), 1999, pp. xxxv+286; Rs. 150/